2016
DOI: 10.1242/dev.136432
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide signaling in plant development

Abstract: The membranes of eukaryotic cells create hydrophobic barriers that control substance and information exchange between the inside and outside of cells and between cellular compartments. Besides their roles as membrane building blocks, some membrane lipids, such as phosphoinositides (PIs), also exert regulatory effects. Indeed, emerging evidence indicates that PIs play crucial roles in controlling polarity and growth in plants. Here, I highlight the key roles of PIs as important regulatory membrane lipids in pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
144
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(146 citation statements)
references
References 129 publications
(138 reference statements)
1
144
0
1
Order By: Relevance
“…In Arabidopsis , the major PA molecular species, including 34:2, 34:3, and 36:5, increased compared with its control after salt treatment (Yu et al, ). PI is the precursor of phosphoinositides, which serve as signaling molecules and have involvement in membrane trafficking processes (Heilmann, ; Hou, Ufer, & Bartels, ). Phosphoinositides could regulate ion channels, including potassium channels, affecting nutrient uptake and transport (Hille, Dickson, Kruse, Vivas, & Suh, ).…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis , the major PA molecular species, including 34:2, 34:3, and 36:5, increased compared with its control after salt treatment (Yu et al, ). PI is the precursor of phosphoinositides, which serve as signaling molecules and have involvement in membrane trafficking processes (Heilmann, ; Hou, Ufer, & Bartels, ). Phosphoinositides could regulate ion channels, including potassium channels, affecting nutrient uptake and transport (Hille, Dickson, Kruse, Vivas, & Suh, ).…”
Section: Discussionmentioning
confidence: 99%
“…The very low abundant phosphoinositides (PIs) are important players for the recruitment of peripheral proteins to membranes (Balla, 2013;Heilmann, 2016). PIs are mono-, bis-and tris-phosphorylated derivatives of phosphatidylinositol (PtdIns) and PI compositions differ between the plasma membrane and different organellar membranes (Balla, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This distribution patterns at least to some extent coincide with the subcellular localization of the individual kinases catalyzing PI-synthesis and the phenotypes of the respective knock-out mutants [234,235]. Overall, the general conclusion is that the delivery/retrieval of vesicles to and from the PM is accompanied with a progressively increasing degree of phosphorylation (PtdIns→PtdIns4P→PtdIns(4,5)P 2 ) in subsequent membranes [234]. It appears that PIs in plants are also involved in controlling the central machinery for membrane trafficking and protein sorting.…”
Section: Secretory Trafficking Pathwaymentioning
confidence: 81%
“…Analysis with fluorescent probes specific for particular species of PtdIns revealed that PtdIns(4,5)P 2 is predominantly present in the PM at the tip of growing root hairs upon salt stress, PtdIns3P in motile membranous structures, or tonoplast and PtdIns4P in the TGN and the PM [231,232,233]. This distribution patterns at least to some extent coincide with the subcellular localization of the individual kinases catalyzing PI-synthesis and the phenotypes of the respective knock-out mutants [234,235]. Overall, the general conclusion is that the delivery/retrieval of vesicles to and from the PM is accompanied with a progressively increasing degree of phosphorylation (PtdIns→PtdIns4P→PtdIns(4,5)P 2 ) in subsequent membranes [234].…”
Section: Secretory Trafficking Pathwaymentioning
confidence: 99%
See 1 more Smart Citation